PENGARUH PENDIDIKAN TERHADAP KINERJA PEGAWAI DI DINAS PENDIDIKAN KABUPATEN PANGKEP - Noviana. H, Nurfajria; Hakim, Lukman; Sudarmi, Sudarmi (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACTThis study aims to determine the respondents' responses to the influence of education on employee performance at the Pangkep District Education Office. The type of research used is quantitative research with descriptive research type. The sampling technique used is a saturated sample with the measurement of the research instrument, namely; likert's scale. The data analysis techniques used are descriptive statistical analysis techniques and simple regression analysis techniques with the help of SPSS software applications.Based on the results of research with descriptive statistical analysis, the results of respondents' responses were 88.20% which showed that the level of education in the assessment was very good and respondents' responses to employee performance obtained results of 88.5% which showed that the performance of employees at the Pangkep Regency Education Office was classified as very good. The results of the regression equation can be interpreted based on the t value, it is known that the t value is 60,612 t table 2,024, so it can be concluded that the education level variable (X) has an effect on employee performance (Y) at the Pangkep Regency Education Office.Keywords: Education, Performance, Employees